Snapshots in obstetrics & gynecology - Saxena, Richa; Chacko, José (New Delhi : Japee Brothers Medical Publishers, 2012)
This book "Snapshots in Obstetrics and Gynecology" aims at simplifying the subject of obstetrics and gynecology as much as possible. The idea behind "snapshots" is to present all important topics in obstetrics and gynecology, which are encountered in the clinical practice in form of brief snippets and snapshots. The book has been broadly divided into two sections-obstetrics and gynecology. The section on obstetrics has 5 Chapters, while the section on gynecology has 10 Chapters.
Tiene como objetivo simplificar el tema de la obstetricia y la ginecología tanto como sea posible. La idea detrás de las "instantáneas" es presentar todos los temas importantes en obstetricia y ginecología que se encuentran en la práctica clínica en forma de breves fragmentos e instantáneas. El libro se ha dividido ampliamente en dos secciones: obstetricia y ginecología. La sección de obstetricia tiene 5 Capítulos, mientras que la sección de ginecología tiene 10 Capítulos.
Contents Section I: Obstetrics Section Ii: Gynecology
Keywords: GINECOLOGÍA; OBSTETRICIA